Anaesthesia care team improves outcomes in surgical patients compared with solo anaesthesiologist: An observational study. Issue 1 (January 2019) - Dony, Philippe; Seidel, Laurence; Pirson, Magali; Forget, Patrice
Abstract : BACKGROUND: In anaesthesiology, little attention has been drawn to the role of anaesthesia nurses as support personnel on quality of care. OBJECTIVES: To compare an anaesthesiologist alone (solo anaesthesiologist) with an anaesthesia care team (anaesthesiologist and anaesthesia nurse). DESIGN: An observational study. SETTING: A single centre study. PARTICIPANTS: Anaesthesiologists and anaesthesia nurses. INTERVENTION: Anaesthesia performed by solo anaesthesiologists compared with anaesthesia care teams. MAIN OUTCOME MEASURES: 30-day postoperative mortality and hospital length of stay. Propensity score matching was performed by logistic regression to adjust for baseline differences between the two groups and pairs of perfectly matched patients were formed. RESULTS: Anaesthesia was performed by solo anaesthesiologists in 2832 patients and by an anaesthesia care team in 2842 patients. Matching with 2095 pairs of perfectly matched patients was formed. The two groups were comparable in respect of sex and duration of anaesthesia but differed notably for age, American Society of Anesthesiologists' physical status score and type of surgery. Logistic regression showed a significantly lower 30-day mortality rate for the anaesthesia care teams compared with solo anaesthesiologists (0.76 vs. 1.56%, P = 0.0014). Length of hospital stay was also significantly reduced when an anaesthesia nurse was present (4.9 ± 10.1 vs. 5.6 ± 11.5 days, P = 0.0011). CONCLUSION: Anaesthesia given by teams of anaesthesiologists and anaesthesia nurses is associated with decreased 30-day postoperative mortality and shorter length of stay when compared with solo anaesthesiologists. Even without any demonstration of causality, this emphasises the benefits of the anaesthesia care team model. TRIAL REGISTRATION: CCB 325201730849. Abstract : Supplemental Digital Content is available in the text